A preparation method and application of biomass carbon microsphere material
The biomass carbon microspheres are prepared by hydrothermal method and high-temperature calcination. The existing biomass carbon materials are solved, and the existing biomass carbon materials are low energy density and short cycle life in lithium/sodium ion battery applications are achieved, and a high-performance lithium/sodium ion battery negative electrode material is achieved.
Patent Information
- Application Number
- CN202310298638.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-03-24
AI Technical Summary
The existing biomass-derived carbon materials have defects such as low energy density and short cycle life in lithium/sodium ion battery applications, which limit their industrial applications.
Fresh lotus roots are used as raw materials, reacted with additives through hydrothermal method to obtain a precursor, and then calcined at high temperature in an inert atmosphere, and finally washed with hydrochloric acid and water alcohol to prepare biomass carbon microsphere material.
The specific capacity, circulation performance and rate performance of the negative electrode material of lithium/sodium ion battery is improved, and the preparation method is simple and low-cost, which is suitable for industrial production.
Smart Images

Figure CN116282007B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomass derived carbon, and more specifically, relates to a preparation method and application of a biomass carbon microsphere material. Background Art
[0002] With the continuous innovation of industrial technology and the rapid development of social economy, the consumption rate of fossil energy such as coal, oil and natural gas has increased sharply, which has also brought many problems such as environmental pollution and global warming, seriously threatening people's health. Based on this, people have begun to turn their attention to the development of renewable green energy such as wind energy, solar energy and tidal energy. However, renewable green energy is easily affected by factors such as climate and seasons during its application, so it must be matched with energy storage / conversion devices to ensure that it can be used stably.
[0003] Secondary batteries (lithium / sodium ion batteries) are energy storage devices that can achieve efficient conversion of electrical energy and chemical energy and have been widely used in people's production and life. However, to achieve the long-term development and widespread application of lithium / sodium ion batteries, higher requirements must be placed on them, and factors such as electrochemical performance, safety performance and cost must be fully considered. Among them, the negative electrode material directly affects the specific capacity and cycle stability of the battery. Therefore, the negative electrode material must have excellent electrochemical performance, low price, environmental friendliness, easy availability and high stability.
[0004] Carbon materials have attracted the attention of many researchers due to their unique one-dimensional to three-dimensional network structure, good electronic conductivity, natural abundance and strong mechanical properties. In addition, there are many types of carbon materials, including fullerenes, carbon nanotubes, graphene, mesoporous carbon and composite materials, which provide a variety of options for negative electrode materials of lithium / sodium ion batteries. However, the above carbon materials have the disadvantages of high production cost and difficulty in large-scale production. Biomass-derived carbon materials are highly aromatic carbon-rich solid powder materials obtained by pyrolyzing biomass raw materials under anaerobic or anaerobic conditions. It has the advantages of abundant sources, simple preparation methods, acid and alkali resistance, high temperature resistance, and good conductivity. In addition, although the obtained biomass carbon materials have a large specific surface area and a complex pore structure, they have defects such as low energy density and short cycle life in the application process of lithium / sodium ion batteries, which seriously limit their actual industrial application.
[0005] Based on the defects of current biomass-derived carbon materials, providing a high-performance biomass-derived carbon material for lithium / sodium ion battery negative electrode material to improve battery performance is an urgent problem to be solved by technicians in this field. Summary of the invention
[0006] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0007] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a biomass carbon microsphere material is provided, comprising the following steps:
[0008] Step 1, wash and dry the fresh lotus root, crush and sieve to obtain lotus root powder;
[0009] Step 2: hydroheating the lotus root powder obtained in step 1 and the additive in a reaction kettle to obtain a precursor;
[0010] Step 3: calcining the precursor in step 2 at high temperature in a tubular furnace with an inert protective gas, and then cooling naturally to room temperature to obtain an activated carbonized material;
[0011] Step 4: soak the activated carbonized material in step 3 with hydrochloric acid, then wash it with distilled water and ethanol, and then dry it to obtain the biomass carbon microsphere material.
[0012] Preferably, the additive in step 2 is one or more of urea, phosphoric acid, and diammonium phosphate.
[0013] Preferably, in step 2, the mass ratio of lotus root powder to the additive used is 3:1-2.
[0014] Preferably, the hydrothermal temperature in step 2 is 160-200°C.
[0015] Preferably, the hydrothermal time in step 2 is 4 to 8 hours.
[0016] Preferably, the inert protective gas during the high-temperature calcination treatment in step three is nitrogen or argon, the carbonization temperature is 300-500° C., and the insulation time is 1-3 hours.
[0017] Preferably, the concentration of hydrochloric acid in step 4 is 1.0 mol L -1 .
[0018] Preferably, the additive in step 2 is melamine or dicyandiamide, and the lotus root powder and the additive are subjected to high-temperature pyrolysis reaction in a reactor to prepare a precursor. The specific method includes: mixing the lotus root powder and the additive, first heating at 5-10°C min -1 The heating rate is raised to 120-150℃, kept at this temperature for 10-20min, and then heated at 10-15℃min -1 The heating rate is raised to 260-300℃, kept at this temperature for 30-40min, and then heated at 20-25℃min -1The temperature is raised to 500-700°C at a heating rate of 1000°C, kept at this temperature for 15-25 minutes, and then cooled to room temperature to obtain material A;
[0019] Loading TiO on material A 2 The specific steps include: weighing 80-400g of tetrabutyl titanate by weight, mixing the tetrabutyl titanate with 2800mL of ethanol solution, wherein the mass fraction of ethanol is 70%, magnetic stirring, and the stirring speed is 100-500rpm. While magnetic stirring, glacial acetic acid is added dropwise to the solution. After gel is generated in the solution, weighing 400-1500g of material A is added to the solution, and magnetic stirring is continued. The magnetic stirring speed is adjusted to 200-450rpm. The generated TiO 2 The mixture is adsorbed on the surface of the nitrogen-doped activated carbonized material, filtered and dried to obtain a mixture, and the mixture is subjected to a hydrothermal reaction in a reactor, and then taken out and dried to obtain a precursor.
[0020] An application of a method for preparing a biomass carbon microsphere material comprises the following steps:
[0021] S1. Weigh the materials in a mass ratio of biomass carbon microsphere material: acetylene black: polyvinylidene fluoride = 8:1:1, add N-methylpyrrolidone, mix evenly, stir into a paste, and then apply it on the copper foil. The amount of N-methylpyrrolidone added is enough to grind the biomass carbon material, acetylene black, and polyvinylidene fluoride emulsion into an ink-like state;
[0022] S2, drying and cutting the copper foil coated with the biomass carbon microsphere material obtained in S1 to obtain a negative electrode sheet for a lithium / sodium ion battery;
[0023] S3. Assemble the negative electrode sheets of the lithium / sodium ion battery obtained in S2 into CR2016 button batteries in a glove box.
[0024] The present invention includes at least the following beneficial effects: the present invention uses fresh lotus root, washes it, dries it, and then crushes and sieves it to obtain its powder; then the powder and additives are hydrothermally treated in a reactor to obtain a precursor; finally, the precursor is calcined at high temperature in a tubular furnace with an inert protective gas, and then naturally cooled to room temperature to obtain a biomass carbon microsphere material. The additives added in the hydrothermal process provide heteroatoms, wherein the introduction of heteroatoms is a method of increasing capacity, and also improves the surface wettability and electronic conductivity of carbon materials, which can promote charge transfer and the interaction between electrodes and electrolytes. In addition, the carbonization process is carried out in an inert gas atmosphere, which can make the material more uniform and stable. Some gases are often released during the pyrolysis of biomass materials, such as CO, CH 4 , H 2 and H 2O, etc., and the remaining substances are converted into amorphous carbon at high temperature. Finally, the biomass carbon microspheres prepared by hydrothermal and carbonization not only contain rich N / P elements, which are beneficial to improve the storage capacity and related dynamics of lithium / sodium; at the same time, the small-sized spherical structure with a diameter of 3-4 mm is also conducive to the rapid intercalation / deintercalation of lithium / sodium ions.
[0025] The biomass carbon microsphere material prepared by the present invention is a lithium / sodium ion battery negative electrode with good electrochemical performance, which has a large specific capacity, good cycle performance and rate performance, and also has the advantages of simple preparation method and low cost, which is conducive to industrial production.
[0026] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 XRD diffraction patterns of biomass carbon materials prepared in Example 2, Example 5 and Example 9;
[0028] Figure 2 The Raman scattering spectra of the biomass carbon materials prepared in Example 2, Example 5 and Example 9;
[0029] Figure 3 In order to perform N on the biomass carbon materials obtained in Example 2, Example 5 and Example 9 2 Schematic diagram of adsorption / desorption test results;
[0030] Figure 4 The pore size distribution diagram of the biomass carbon materials prepared in Example 2, Example 5 and Example 9;
[0031] Figure 5 The SEM morphology characterization images of the biomass carbon materials prepared in Example 2, Example 5 and Example 9;
[0032] Figure 6 The XPS graphs of the biomass carbon materials prepared in Example 2, Example 5 and Example 9;
[0033] Figure 7 A schematic diagram of the first charge-discharge curve of lithium storage of biomass carbon materials prepared in Example 2, Example 5 and Example 9;
[0034] Figure 8 Schematic diagram of lithium storage rate and cycle of biomass carbon materials prepared in Example 2, Example 5 and Example 9;
[0035] Fig. 9 This is a schematic diagram of the charge-discharge curves of the first three cycles of sodium storage of the biomass carbon microsphere material prepared in Example 9;
[0036] Fig.10 This is a schematic diagram of the sodium storage long cycle of the biomass carbon microsphere material prepared in Example 9;
[0037] Fig.11 The biomass carbon materials obtained in Examples 9, 13 and 14 were subjected to N 2 Schematic diagram of adsorption / desorption test results. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0039] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0040] Embodiment 1:
[0041] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0042] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0043] Step 2: weigh and mix the powder obtained in step 1 with urea in a mass ratio of 3:1, and then disperse by ultrasonication;
[0044] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 160° C. for 6 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0045] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 300℃, keep warm for 2h;
[0046] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material was soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which was recorded as LRN1.
[0047] Embodiment 2:
[0048] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0049] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0050] Step 2: weigh and mix the powder obtained in step 1 with urea in a mass ratio of 3:1, and then disperse by ultrasonication;
[0051] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 180° C. for 6 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0052] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 400℃, keep warm for 2h;
[0053] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material is soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which is recorded as LRN2.
[0054] Embodiment 3:
[0055] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0056] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0057] Step 2: weigh and mix the powder obtained in step 1 with urea in a mass ratio of 3:2, and then disperse by ultrasonication;
[0058] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 180° C. for 8 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0059] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 500℃, keep warm for 2h;
[0060] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material was soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which was recorded as LRN3.
[0061] Embodiment 4:
[0062] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0063] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0064] Step 2: weigh and mix the powder obtained in step 1 with phosphoric acid in a mass ratio of 3:1, and then disperse by ultrasonication;
[0065] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 160° C. for 8 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0066] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 300℃, keep warm for 2h;
[0067] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material was soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which was recorded as LRP1.
[0068] Embodiment 5:
[0069] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0070] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0071] Step 2: weigh and mix the powder obtained in step 1 with phosphoric acid in a mass ratio of 3:1, and then disperse by ultrasonication;
[0072] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 180° C. for 6 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0073] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 400℃, keep warm for 2h;
[0074] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material was soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which was recorded as LRP2.
[0075] Embodiment 6:
[0076] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0077] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0078] Step 2: weigh and mix the powder obtained in step 1 with phosphoric acid in a mass ratio of 3:2, and then disperse by ultrasonication;
[0079] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 160° C. for 6 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0080] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 500℃, keep warm for 2h;
[0081] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material was soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which was recorded as LRP3.
[0082] Embodiment 7:
[0083] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0084] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0085] Step 2: weigh and mix the powder obtained in step 1 with urea / phosphoric acid in a mass ratio of 3:1:1, and then disperse by ultrasonication;
[0086] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 160° C. for 6 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0087] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 300℃, keep warm for 2h;
[0088] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material was soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which was recorded as LRNP1.
[0089] Embodiment 8:
[0090] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0091] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0092] Step 2: weigh and mix the powder obtained in step 1 with urea / phosphoric acid in a mass ratio of 3:1:2, and then disperse by ultrasonication;
[0093] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 160° C. for 8 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0094] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 400℃, keep warm for 2h;
[0095] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material is soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which is recorded as LRNP2.
[0096] Embodiment 9:
[0097] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0098] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0099] Step 2: weigh and mix the powder obtained in step 1 with urea / phosphoric acid in a mass ratio of 3:1:1, and then disperse by ultrasonication;
[0100] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 180° C. for 6 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0101] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 400℃, keep warm for 2h;
[0102] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1The obtained material was soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which was recorded as LRNP3.
[0103] Embodiment 10:
[0104] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0105] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0106] Step 2: weigh and mix the powder obtained in step 1 with urea / phosphoric acid in a mass ratio of 3:2:1, and then disperse by ultrasonication;
[0107] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 180° C. for 8 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0108] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 500℃, keep warm for 2h;
[0109] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material is soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which is recorded as LRNP4.
[0110] Embodiment 11:
[0111] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0112] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0113] Step 2: weigh and mix the powder obtained in step 1 with urea / phosphoric acid in a mass ratio of 3:2:2, and then disperse by ultrasonication;
[0114] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 160° C. for 8 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0115] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 300℃, keep warm for 2h;
[0116] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material was soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which was recorded as LRNP5.
[0117] Embodiment 12:
[0118] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0119] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0120] Step 2: weigh and mix the powder obtained in step 1 with urea / phosphoric acid in a mass ratio of 3:1:2, and then disperse by ultrasonication;
[0121] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 160° C. for 8 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0122] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 500℃, keep warm for 2h;
[0123] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material was soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which was recorded as LRNP6.
[0124] Embodiment 13:
[0125] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0126] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0127] Step 2: Prepare a precursor by high temperature pyrolysis reaction of lotus root powder and melamine in a reactor at a mass ratio of 3:1. The specific method includes: mixing lotus root powder and melamine at 5°C min -1 The temperature was raised to 120℃ at a rate of 10℃min. -1 The temperature was raised to 260℃ at a heating rate of 20℃min. -1 The temperature was raised to 500°C at a heating rate of , kept at that temperature for 15 min, and then cooled to room temperature to obtain material A;
[0128] Loading TiO on material A 2 The specific steps include: weighing 80g of tetrabutyl titanate by weight, mixing the tetrabutyl titanate with 2800mL of ethanol solution, wherein the mass fraction of ethanol is 70%, magnetic stirring, and the stirring speed is 100rpm. While magnetic stirring, glacial acetic acid is added dropwise to the solution. After gel is generated in the solution, weighing 400g of material A is added to the solution, and magnetic stirring is continued. The magnetic stirring speed is adjusted to 200rpm. The generated TiO 2 It is adsorbed on the surface of nitrogen-doped activated carbonized material, filtered and dried to obtain a mixture;
[0129] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 180° C. for 6 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0130] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 400℃, keep warm for 2h;
[0131] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material is soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which is recorded as LRN4.
[0132] Embodiment 14:
[0133] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0134] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0135] Step 2: Prepare a precursor by high temperature pyrolysis reaction of lotus root powder and melamine in a reaction kettle at a mass ratio of 3:1. The specific method includes: mixing lotus root powder and melamine, first heating at 8℃min -1 The temperature was raised to 130℃ at a rate of 13℃min. After keeping the temperature for 15min, the temperature was raised to 130℃ at a rate of 13℃min. -1 The temperature was raised to 280℃ at a rate of 22℃min. -1 The temperature was raised to 600°C at a heating rate of , kept at that temperature for 20 minutes and then cooled to room temperature to obtain material A;
[0136] Loading TiO on material A 2The specific steps include: weighing 150g of tetrabutyl titanate by weight, mixing the tetrabutyl titanate with 2800mL of ethanol solution, wherein the mass fraction of ethanol is 70%, magnetic stirring, and the stirring speed is 300rpm. While magnetic stirring, glacial acetic acid is added dropwise to the solution. After gel is generated in the solution, weighing 400g of material A and adding it to the solution, continuing magnetic stirring, and adjusting the magnetic stirring speed to 300rpm. The generated TiO 2 It is adsorbed on the surface of nitrogen-doped activated carbonized material, filtered and dried to obtain a mixture;
[0137] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 180° C. for 6 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0138] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 400℃, keep warm for 2h;
[0139] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material was soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which was recorded as LRN5.
[0140] Embodiment 15:
[0141] A method for preparing a biomass carbon microsphere material, the operating steps are as follows:
[0142] Step 1: Wash and dry the fresh lotus root, crush it and sieve it to obtain powder;
[0143] Step 2: Prepare a precursor by high temperature pyrolysis reaction of lotus root powder and melamine in a reaction kettle at a mass ratio of 3:1. The specific method includes: mixing lotus root powder and melamine, first heating at 10℃min -1 The temperature was raised to 150°C at a rate of 15°C min-1, and then kept at this temperature for 20 min. -1 The temperature was raised to 300℃ at a heating rate of 25℃min. -1 The temperature was raised to 700°C at a heating rate of , kept at that temperature for 25 minutes, and then cooled to room temperature to obtain material A;
[0144] Loading TiO on material A 2The specific steps include: weighing 400g of tetrabutyl titanate by weight, mixing the tetrabutyl titanate with 2800mL of ethanol solution, wherein the mass fraction of ethanol is 70%, magnetic stirring, and the stirring speed is 500rpm. While magnetic stirring, glacial acetic acid is added dropwise to the solution. After gel is generated in the solution, weighing 1500g of material A and adding it to the solution, continuing magnetic stirring, and adjusting the magnetic stirring speed to 450rpm. The generated TiO 2 It is adsorbed on the surface of nitrogen-doped activated carbonized material, filtered and dried to obtain a mixture;
[0145] Step 3: subjecting the mixture obtained in step 2 to a hydrothermal reaction in a reactor at a temperature of 180° C. for 6 hours, and after the reaction is completed, taking out and drying to obtain a precursor;
[0146] Step 4: Place the precursor in step 3 in a quartz boat and control the gas flow rate to 100 mL min under a nitrogen atmosphere. -1 and the heating rate was 5℃min -1 , calcination temperature is 400℃, keep warm for 2h;
[0147] Step 5: After the calcined material has cooled to room temperature, 1.0 mol L -1 The obtained material is soaked in hydrochloric acid, then repeatedly washed with distilled water and ethanol, and finally dried to obtain the biomass carbon microsphere material, which is recorded as LRN6.
[0148] Application Example 1:
[0149] This application example uses the LRN2 material prepared in Example 2 to prepare a negative electrode sheet for a lithium / sodium battery, including the following steps:
[0150] S1. Weigh the materials in a mass ratio of LRN2 material: acetylene black: polyvinylidene fluoride = 8:1:1, add N-methylpyrrolidone, mix evenly, stir into a paste, and then apply it on the copper foil. The amount of N-methylpyrrolidone added is enough to grind the biomass carbon material, acetylene black, and polyvinylidene fluoride emulsion into an ink-like state;
[0151] S2, drying and cutting the copper foil coated with the biomass carbon microsphere material obtained in S1 to obtain a negative electrode sheet for a lithium / sodium ion battery;
[0152] S3. Assemble the negative electrode sheets of the lithium / sodium ion battery obtained in S2 into CR2016 button batteries in a glove box.
[0153] Application Example 2:
[0154] This application example uses the LRP2 material prepared in Example 5 to prepare a negative electrode sheet for a lithium / sodium battery, including the following steps:
[0155] S1. Weigh the materials at a mass ratio of LRP2 material: acetylene black: polyvinylidene fluoride = 8:1:1, add N-methylpyrrolidone, mix evenly, stir into a paste, and then apply it on the copper foil. The amount of N-methylpyrrolidone added is enough to grind the biomass carbon material, acetylene black, and polyvinylidene fluoride emulsion into an ink-like state;
[0156] S2, drying and cutting the copper foil coated with the biomass carbon microsphere material obtained in S1 to obtain a negative electrode sheet for a lithium / sodium ion battery;
[0157] S3. Assemble the negative electrode sheets of the lithium / sodium ion battery obtained in S2 into CR2016 button batteries in a glove box.
[0158] Application Example 3:
[0159] This application example uses the LRNP3 material prepared in Example 9 to prepare a negative electrode sheet for a lithium / sodium battery, including the following steps:
[0160] S1. Weigh the materials in a mass ratio of LRNP3 material: acetylene black: polyvinylidene fluoride = 8:1:1, add N-methylpyrrolidone, mix evenly, stir into a paste, and then apply it on the copper foil. The amount of N-methylpyrrolidone added is enough to grind the biomass carbon material, acetylene black, and polyvinylidene fluoride emulsion into an ink-like state;
[0161] S2, drying and cutting the copper foil coated with the biomass carbon microsphere material obtained in S1 to obtain a negative electrode sheet for a lithium / sodium ion battery;
[0162] S3. Assemble the negative electrode sheets of the lithium / sodium ion battery obtained in S2 into CR2016 button batteries in a glove box.
[0163] Application example 4:
[0164] This application example uses the LRN4 material prepared in Example 13 to prepare a negative electrode sheet for a lithium / sodium battery, including the following steps:
[0165] S1. Weigh the materials in a mass ratio of LRN4 material: acetylene black: polyvinylidene fluoride = 8:1:1, add N-methylpyrrolidone, mix evenly, stir into a paste, and then apply it on the copper foil. The amount of N-methylpyrrolidone added is enough to grind the biomass carbon material, acetylene black, and polyvinylidene fluoride emulsion into an ink-like state;
[0166] S2, drying and cutting the copper foil coated with the biomass carbon microsphere material obtained in S1 to obtain a negative electrode sheet for a lithium / sodium ion battery;
[0167] S3. Assemble the negative electrode sheets of the lithium / sodium ion battery obtained in S2 into CR2016 button batteries in a glove box.
[0168] The prepared biomass carbon microspheres were characterized by X-ray diffraction (XRD). Figure 1 As shown. LRN2, LRP2 and LRNP3 samples have two broad diffraction peaks near 24.89° and 43.45°, which correspond to the (002) and (100) plane reflections of disordered carbon, respectively, revealing the disordered characteristics of the material. The average interlayer spacing (d 002 ) reaches 0.358nm, which is larger than the interlayer spacing of graphite 0.335nm; it can alleviate the Li + The volume expansion during the intercalation / deintercalation process enables high current charging and discharging; it is also beneficial to Na + Rapid adsorption and deintercalation.
[0169] In order to better understand the order of the research materials, Raman scattering spectroscopy tests were performed on LRN2, LRP2 and LRNP3. The results are as follows Figure 2 As shown. Raman spectrum at 1357cm -1 (D belt) and 1596cm -1 (G band) has two obvious peaks. Defects and disorder cause the generation of D peak, while all sp 2 The stretching motion of the atomic pairs produces the G peak. The intensity ratio of the D peak to the G peak is generally used to measure the defect density and edge density of carbon materials. The intensity ratios of the D peak to the G peak of LRN2, LRP2 and LRNP3 are 0.67, 0.73 and 0.80, respectively. The results show that the doping of N / P elements will produce more defects, thus + / Na + Adsorption and embedding provide more active sites.
[0170] In order to study the specific surface area and pore size distribution of the materials, LRN2, LRP2 and LRNP3 were subjected to N 2 Adsorption / desorption test. Figure 3 As shown in the figure, the adsorption-desorption isotherms of the three samples all have composite characteristics of type I, type IV and type II, with obvious H3 hysteresis loops, indicating that the three materials are porous carbon materials with hierarchical structures of micropores, mesopores and macropores. According to the BET calculation results, the specific surface areas of LRN2, LRP2 and LRNP3 are 338.025, 379.117 and 461.645 m 2 g -1 , indicating that the dual-element doped spherical structure has the largest specific surface area, which can provide more active sites for the electrolyte contact interface and charge transfer reaction. Figure 4The distribution of mesopores is calculated by BJH. Mesopores are both storage spaces for lithium ions and channels connecting the electrolyte and the interior of the material. This is what determines the Li + / Na + The key factor for fast transmission.
[0171] The morphology of LRN2, LRP2 and LRNP3 was characterized by SEM. Figure 5 As shown in (af), all samples showed a three-dimensional particle array with interconnected morphology, while LRNP3 was a combination of small particles in LRN2 and LRP2 into a more regular sphere.
[0172] The element contents of LRN2, LRP2 and LRNP3 were determined by XPS. Figure 6 As shown. It can be seen that the three materials mainly contain C, O, and N elements, and the presence of P is mainly provided by the additive phosphoric acid, because the biomass material itself also contains a small amount of N element. The dual doping of N and P elements has an outstanding synergistic effect on improving the compatibility of carbon and electrolyte, which can give it ultrafast charge storage kinetics and excellent electrochemical performance.
[0173] Figure 7 The voltage range of LRN2, LRP2 and LRNP3 is 0.01~3.0V and 0.05Ag respectively. -1 The first charge and discharge curve under current density. As can be seen from the figure, LRN2 (1289.85mAh g -1 )、LRP2(1401.77mAh g -1 ) and LRNP3 (1794.25mAh g -1 ) have a higher initial discharge capacity. However, their initial charge capacity is only 643.03 mAh g -1 、704.97mAh g -1 and 954.39mAh g -1 , the corresponding initial coulombic efficiencies are 49.85%, 50.30% and 53.19%. These results mean that the doping of high electronegativity N and low electronegativity P synergistically activates the π electrons of the graphene unit, making the N / P co-doped carbon material have excellent electrochemical properties; at the same time, the co-doped P functional group can also improve the wettability of the carbon material to the electrolyte and provide it with more electroactive sites; in addition, the synergistic effect of the porous structure and element doping greatly improves the lithium storage performance of the material.
[0174] Figure 8The rate performance of LRN2, LRP2 and LRNP3 materials in the voltage range of 0.01-3.0V and different current densities. It can be seen from the figure that the rate performance of LRNP3 is better than that of LRN2 and LRP2, indicating that the excellent electrochemical performance of N and P dual-doped biomass carbon microspheres can be attributed to the synergistic effect of hierarchical pore structure and uniform heteroatom (N and P) doping. N and P groups serve as effective electroactive sites for rapid regulation / relaxation of protons or electrons, while the hierarchical pore structure is dedicated to the rapid ion diffusion of electrolytes.
[0175] Fig. 9 and Fig.10 LRNP3 material has a voltage range of 0.01 to 3.0 V and a 0.05Ag -1 With 0.5Ag -1 The first three cycles of charge and discharge curves and long cycle diagram under current density. It can be seen that the first charge and discharge also has a low coulombic efficiency (53.48%); at the end of the long cycle, LRNP3 still maintains 204.60mAh g -1 The high reversible specific capacity and the coulombic efficiency remain at around 99.26%, showing good sodium storage capacity.
[0176] Fig.11 N was performed using LRNP3, LRN4, and LRN5 2 Schematic diagram of the results of the adsorption / desorption test, it can be seen that LRN4 and LRN5 prepared in Example 13 and Example 14 have better N 2 Adsorption effect.
[0177] As described above, the biomass carbon microspheres prepared by the present invention not only have multi-element doping, but also have a rich porous structure, which has an outstanding synergistic effect on improving the compatibility of carbon and electrolyte, and can give it ultra-fast charge storage kinetics and excellent electrochemical performance. At the same time, due to the advantages of low precursor cost and simple synthesis method of this material, it can also have good application prospects in other next-generation energy storage devices such as supercapacitors and secondary alkali metal batteries.
[0178] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.
[0179] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. An energy storage application of biomass carbon microsphere material, characterized in that: The following steps are involved: S1. Weigh the materials in a mass ratio of 8:1:1 for biomass carbon microsphere material: acetylene black: polyvinylidene fluoride, and add N-methylpyrrolidone, mix evenly, stir into a paste, and then apply it on the copper foil by scraping. The amount of N-methylpyrrolidone added is enough to grind the biomass carbon material, acetylene black, and polyvinylidene fluoride emulsion into an ink-like state. S2, drying and cutting the copper foil coated with the biomass carbon microsphere material obtained in S1 to obtain a negative electrode sheet for a lithium / sodium ion battery; S3, assembling the lithium / sodium ion battery negative electrode sheet obtained in S2 into a CR2016 button battery in a glove box; The method for preparing the biomass carbon microsphere material comprises the following steps: Step 1, wash and dry the fresh lotus root, crush and sieve to obtain lotus root powder; Step 2: Mix the lotus root powder and additives and heat at 5~10℃ for 10min. -1 The heating rate is raised to 120~150℃, kept at this temperature for 10~20min, and then heated at 10~15℃ min -1 The heating rate is raised to 260~300℃, kept at this temperature for 30~40min, and then heated at 20~25℃ min -1 The temperature is raised to 500-700°C at a heating rate of 10000 °C, kept at this temperature for 15-25 min, and then cooled to room temperature to obtain material A; the additive is melamine or dicyandiamide; the mass ratio of lotus root powder to the additive is 3:1-2; Weigh 80-400 g of tetrabutyl titanate, mix the tetrabutyl titanate with 2800 mL of ethanol solution, the mass fraction of ethanol is 70%, and stir magnetically at 100-500 rpm. While stirring magnetically, add glacial acetic acid to the solution. After gel is generated in the solution, weigh 400-1500 g of material A and put it into the solution. Adjust the magnetic stirring speed to 200-450 rpm. The generated TiO2 is adsorbed on the surface of the nitrogen-doped activated carbonized material. Filter and dry to obtain a mixture. Perform a hydrothermal reaction on the mixture in a reactor. The hydrothermal temperature is 160-200 °C and the hydrothermal time is 4-8 h. Take out and dry to obtain a precursor. Step 3: calcining the precursor at high temperature in a tubular furnace with an inert protective gas, and then cooling it naturally to room temperature to obtain an activated carbonized material; the inert protective atmosphere during the high-temperature calcination treatment is nitrogen or argon, the calcination temperature is 300-500°C, and the holding time is 1-3 hours; Step 4: Activate the carbonized material with 1.0 mol L -1 The biomass carbon microsphere material is obtained by soaking in hydrochloric acid, washing with distilled water and ethanol, and then drying.
Citation Information
Patent Citations
Method for preparing porous carbon spheres from biomass raw materials
CN113387355A
Preparation method and energy storage application of graded porous biomass carbon material
CN115028167A
Heteroatom doped biomass derived hard carbon negative electrode material and preparation method thereof
CN115385323A
Preparation method and energy storage application of titanium dioxide / heteroatom doped porous carbon material
CN115732663A